Immunogenicity and diagnostic potential of synthetic antigenic cell surface glycans of leishmania - Anish, Chakkumkal; Martin, Christopher E.; Wahlbrink, Annette; Bogdan, Christian; Ntais, Pantelis; Antoniou, Maria; Seeberger, Peter H. (ACS Chemical Biology, 2013)
Detection and quantification of pathogen-derived antigenic structures is a key method for the initial diagnosis and follow-up of various infectious diseases. Complex parasitic diseases such as leishmaniasis require highly sensitive and specific tests prior to treatment with potentially toxic drugs. To investigate the diagnostic potential of cell surface glycans found on Leishmania parasites, we identified diagnostically relevant glycan epitopes and used synthetic glycan microarrays to screen sera from infected humans and dogs. On the basis of the screening results, we selected a tetrasaccharide to generate anti-glycan antibodies. The corresponding tetrasaccharide-carrier protein conjugate was immunogenic in mice, and sera obtained from immunized mice specifically detected the Leishmania parasite. These results demonstrate how synthetic glycan arrays, in combination with immunological methods, help to identify promising carbohydrate antigens for pathogen detection. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2024-02-26